Использование контекстных данных при управлении распределенной сетью электропитания - Вербицкий, Е.В.; Киселева, А.Г. (Технічна електродинаміка, 2016)
В статье описаны особенности структуры распределенной сети электропитания на силовом и информационном
уровне. Показана необходимость применения гетерогенных контекстных данных о внешних условиях,
режимах работы силового оборудования и характере нагрузки для управления системой электропитания.
Обоснована целесообразность использования иерархического принципа управления на основе логических правил. В статті описано особливості структури розподіленої мережі електропостачання на силовому та інформаційному
рівні. Показано необхідність використання гетерогенних контекстних даних про зовнішні умови, режи-ми
роботи силового обладнання та характер навантаження для керування системою електроживлення. Обґрунтовано
доцільність використання ієрархічного принципу керування на основі логічних правил. The features of the structure of distributed power grid to the power and data level are described. The necessity of
application of heterogeneous data on external conditions, power equipment operating modes and the characteristic of
the load for network management is shown. The expediency of hierarchical control principle based on logical rules is
substantiated. The necessity of data pre-processing and formalization in form of context in order to reduce the volume
of circulating and processed information is justified. Implementing the procedure of digital filtering, verification and
data forecast allowed reducing the noise and inertia of the control system. The principles of formalization of context,
which reduced the volume of data transmitted and processed were elaborated. The approach of the formation of the
rules allows applying intellectual control algorithms for power system, improving the quality of management.